Arthroscopic Fixation of Comminuted Glenoid Fractures Using Cannulated Screws and Suture Anchors. Issue 49 (December 2015) - Qu, Feng; Yuan, Bangtuo; Qi, Wei; Li, Chunbao; Shen, Xuezhen; Guo, Qi; Zhao, Gang; Wang, Jiangtao; Li, Hongliang; Lu, Xi; Liu, Yujie
Abstract : Abstract: We investigate the feasibility of arthroscopic fixation of comminuted glenoid fractures using cannulated screws and suture anchors. We retrospectively review 11 cases of closed comminuted glenoid fractures treated at our institution from August 2010 to May 2013. The 11 patients, 8 males and 3 females, had a mean age of 41 years (range: 27–55 years). The mechanisms of injury were traffic accidents in 9 cases and falls from height in 2 cases. The mean time from injury to surgery was 12 days (range: 3–28 days). All glenoid fractures were confirmed on x-ray and computed tomography. The major fracture fragments were fixed with cannulated screws and the small fragments were fixed with suture anchors. All surgical wounds healed with primary closure and no complications including infection and neurovascular damage were observed. All 11 patients were followed up for a mean of 21 months (range: 14–29 months). Bone union was achieved in all patients with a mean time of 10 months. At the last follow-up, range of motion of the shoulder joint was significantly improved ( P  < 0.05). Both ASES scores (41.4 ± 24.9, 87.3 ± 13.8) and Rowe scores (28.2 ± 18.6, 93.2 ± 11.2) were significantly increased after the surgery ( P  < 0.01), indicating significantly improved function and stability of the shoulder joint. Arthroscopic fixation using cannulated screws and suture anchors is feasible for the treatment of comminuted glenoid fractures. This method is minimally invasive and provides good functional recovery with a lower risk of complications.